24.0k views
3 votes
For the following system, use the second equation to make a substitution for y in the first equation.

3x + y = 1
y + 4 = 5x

What is the resulting equation?

3x + 5x - 4 = 1
3x + 4 - 5x = 1
3x + 5x + 4 = 1

User Amyunimus
by
5.7k points

2 Answers

3 votes

Answer:

3x + 5x - 4 = 1

Explanation:

User Eddy Bayonne
by
5.7k points
0 votes

Answer:

Option A: 3x + 5x - 4 = 1

Explanation:

Given that:

3x + y = 1 ------------- eq1

y + 4 = 5x ------------ eq2

Now for substitution in eq1 we will get a value of y from eq2:

y = 5x - 4

Substituting in eq1 we get:

3x + 5x - 4 = 1

i hope it will help you!

User Lex
by
5.2k points